2006
DOI: 10.1152/ajpcell.00342.2005
|View full text |Cite
|
Sign up to set email alerts
|

The depressive effect of Pi on the force-pCa relationship in skinned single muscle fibers is temperature dependent

Abstract: . The depressive effect of P i on the force-pCa relationship in skinned single muscle fibers is temperature dependent. Am J Physiol Cell Physiol 290: C1041-C1050, 2006. First published November 9, 2005 doi:10.1152/ajpcell.00342.2005.-Increases in P i combined with decreases in myoplasmic Ca 2ϩ are believed to cause a significant portion of the decrease in muscular force during fatigue. To investigate this further, we determined the effect of 30 mM Pi on the force-Ca 2ϩ relationship of chemically skinned singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 59 publications
6
88
0
Order By: Relevance
“…Temperature has previously been shown to modulate the effect of Pi on isometric force in muscle fibers, although there is disagreement about whether Pi is either more [29, 76] or less [77] inhibitory of isometric force as temperature increases. While Pi inhibits isometric force, elevated Pi increases sliding speed for both regulated thin filaments at pCa 5 and unregulated F-actin, although the effect predominates at lower temperatures and is more pronounced for regulated thin-filaments (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature has previously been shown to modulate the effect of Pi on isometric force in muscle fibers, although there is disagreement about whether Pi is either more [29, 76] or less [77] inhibitory of isometric force as temperature increases. While Pi inhibits isometric force, elevated Pi increases sliding speed for both regulated thin filaments at pCa 5 and unregulated F-actin, although the effect predominates at lower temperatures and is more pronounced for regulated thin-filaments (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…It affects several fundamental aspects of muscle structure and function [2224] although temperature effects on muscle function appear to be greater at low temperatures used in many experiments than at physiological temperature; examples are isometric tetanic tension [2527] and maximum mechanical power output [28]. Temperature also modulates the control of striated muscle contraction by Ca 2+ regulatory proteins Tn and Tm, although there are both qualitative and quantitative discrepancies on this point in the striated muscle literature [22, 26, 29, 30]. Interestingly, mild hypothermia has been reported to be a positive inotropic effector in living cardiac muscle due to interplay between temperature and cardiac thin filament Ca 2+ regulation [31].…”
Section: Introductionmentioning
confidence: 99%
“…• C (Debold et al 2006). If pH were to show similar temperature dependence, the force-inhibiting effect of low pH at suboptimal Ca 2+ concentrations might be greater at 30…”
Section: Effect Of Ph On Pmentioning
confidence: 98%
“…First, human studies using isolated muscle exercise in acute hypoxia have shown that a reduced arterial hemoglobin saturation (Sa O 2 ), per se, accelerates the rate of accumulation of fatigue metabolites, which in turn exacerbates the development of peripheral muscle fatigue (20, 29 -31, 36, 37, 39, 42). These detrimental effects of reduced Sa O 2 on fatigue metabolite accumulation and the development of peripheral fatigue are supported by studies on isolated animal muscle fibers (21,27). Second, the W b has also been shown to be a major contributor to the development of locomotor muscle fatigue and to limit exercise performance.…”
mentioning
confidence: 90%